From training to practice: A multi-group analysis of factors influencing K-12 teachers’integration of Digital Educational Resources (DERs) - Qizhong Ou; Songqiao Wu; Yilu Jiang; Zhenni He; Haiqiu Luo (PLoS ONE, 2025)
Ensuring teachers effectively integrate digital technologies is crucial for modernizing education, yet the success of large-scale training initiatives often varies. This study investigates the factors shaping technology adoption among 2,821 K–12 teachers following a national digital literacy program. Using a Structural Equation Model (SEM) based on the UTAUT framework, this research employs a multi-group analysis to examine how adoption drivers differ across key demographic segments. Results show that social influence and performance expectancy are the primary drivers of teachers’ intention to use digital resources, which in turn strongly predicts actual use. Notably, the influence of these factors varies significantly depending on teachers’ regional context, educational stage, and prior digital experience, highlighting the limitations of a uniform approach to professional development. The findings provide a nuanced evidence base for designing more targeted and effective teacher support strategies.